Determination of Mercury Ions Level in River Water Using an Arduino Uno-Based TCS3200 Color Sensor with Silver Nanoparticle Indicators Synthesized from Moringa Oleifera Leaf Extract - Suhud, Khairi; Ningsih, Sri Rahayu; Surbakti, Muhammad Syukri; Hadistya, Muhammad Daffa; Saleha, Sitti; Yusnaidar, Yusnaidar; Hasbullah, Siti Asihah; Omar, Ahmad Fairuz Bin; Fathurrahmi, Fathurrahmi; Damanik, Muhammad Rifki Fauzan; Kacaribu, Andriy Anta (Trends in Sciences, 2025)
Mercury ions (Hg2+) are highly toxic due to their neurotoxic properties. They pose significant risks to organisms and humans, especially when they accumulate in the body and frequently contaminate water. An Arduino Uno-based TCS3200 color sensor utilizing silver nanoparticles (AgNPs) as indicators offer a promising alternative for detecting Hg2+. This approach is characterized by its simplicity, cost-effectiveness, environmental friendliness, and effectiveness for real-time detection in resource-limited areas. This study synthesized AgNPs from the ethyl acetate extract of Moringa oleifera leaves. These AgNPs were tested for selectivity against various metals commonly found in aquatic environments. Once the selective metals were identified, sensitivity and selectivity tests were conducted to confirm that the sensor accurately measures specific analytes, even in the presence of other components within a sample. The results showed that the synthesized AgNPs are highly selective and specific for Hg2+ ions, achieving an accuracy range of 89.3 - 110 %. The sensor can detect Hg2+ ions with a detection limit (DL) of 0.069 ppm. Analysis of river water samples revealed Hg2+ concentrations ranging from 0.128 to 0.287 ppm. Hg2+ concentration was measured using a TCS3200 color sensor and validated against UV-Vis spectrophotometry. This confirmed its comparable results and effectiveness for accurate Hg2+ detection in real-world water samples and resource-limited areas. HIGHLIGHTS Silver nanoparticles (AgNPs) were synthesized from Moringa oleifera leaf extract for mercury detection using a TCS3200 color sensor. High selectivity and sensitivity for Hg2+ ions were achieved, with a detection limit of 0.069 ppm and accuracy of 89.3 - 110 %. The sensor’s performance was validated against UV-Vis spectrophotometry, showing comparable results. The method was applied to river water samples, with Hg2+ concentrations detected between 0.128 and 0.287 ppm, and applicable for real-time monitoring for resource-limited areas. GRAPHICAL ABSTRACT